Respuesta :
To solve this problem you must apply the proccedure shown below:
1. You have the following equation of the line given in the problem above: 2x+3y=11.
2. Therefore, you have:
x=t
3. When you substitute x=t into 2x+3y=11, you obtain:
2t+3y=11
4. Now, solve for y, as below:
3y=11-2t
y=(11/3)-(2t/3)
Therefore, the answer is:
x=t
y=(11/3)-(2t/3)
1. You have the following equation of the line given in the problem above: 2x+3y=11.
2. Therefore, you have:
x=t
3. When you substitute x=t into 2x+3y=11, you obtain:
2t+3y=11
4. Now, solve for y, as below:
3y=11-2t
y=(11/3)-(2t/3)
Therefore, the answer is:
x=t
y=(11/3)-(2t/3)
Answer:
C
Step-by-step explanation:
If youre doing the test ;)